Out of the given choice, the equation represents
.
Answer: Option B
<u>Step-by-step explanation:</u>
We know, ![\csc \theta=\frac{1}{\sin \theta}](https://tex.z-dn.net/?f=%5Ccsc%20%5Ctheta%3D%5Cfrac%7B1%7D%7B%5Csin%20%5Ctheta%7D)
![\sin \theta=\frac{1}{\csc \theta}](https://tex.z-dn.net/?f=%5Csin%20%5Ctheta%3D%5Cfrac%7B1%7D%7B%5Ccsc%20%5Ctheta%7D)
Given data:
![\csc \theta=\frac{8}{7}](https://tex.z-dn.net/?f=%5Ccsc%20%5Ctheta%3D%5Cfrac%7B8%7D%7B7%7D)
So, now sin theta can express as
![\sin \theta=\frac{7(\text { opposite })}{8(\text { Hypotenuse })}](https://tex.z-dn.net/?f=%5Csin%20%5Ctheta%3D%5Cfrac%7B7%28%5Ctext%20%7B%20opposite%20%7D%29%7D%7B8%28%5Ctext%20%7B%20Hypotenuse%20%7D%29%7D)
Sin theta defined by the ratio of opposite to the hypotenuse. In general, the adjacent can be calculated by,
![\text {(opposite) }^{2}+(\text { adjacent })^{2}=(\text {Hypotenuse})^{2}](https://tex.z-dn.net/?f=%5Ctext%20%7B%28opposite%29%20%7D%5E%7B2%7D%2B%28%5Ctext%20%7B%20adjacent%20%7D%29%5E%7B2%7D%3D%28%5Ctext%20%7BHypotenuse%7D%29%5E%7B2%7D)
![7^{2}+(\text { adjacent })^{2}=8^{2}](https://tex.z-dn.net/?f=7%5E%7B2%7D%2B%28%5Ctext%20%7B%20adjacent%20%7D%29%5E%7B2%7D%3D8%5E%7B2%7D)
![(\text {adjacent})^{2}=8^{2}-7^{2}=64-49=15](https://tex.z-dn.net/?f=%28%5Ctext%20%7Badjacent%7D%29%5E%7B2%7D%3D8%5E%7B2%7D-7%5E%7B2%7D%3D64-49%3D15)
Taking square root, we get
![\text { adjacent }=\sqrt{15}](https://tex.z-dn.net/?f=%5Ctext%20%7B%20adjacent%20%7D%3D%5Csqrt%7B15%7D)
Also, we know the formula for cot theta,
![\cot \theta=\frac{1}{\tan \theta}=\frac{1}{\left(\frac{\sin \theta}{\cos \theta}\right)}=\frac{\cos \theta}{\sin \theta}](https://tex.z-dn.net/?f=%5Ccot%20%5Ctheta%3D%5Cfrac%7B1%7D%7B%5Ctan%20%5Ctheta%7D%3D%5Cfrac%7B1%7D%7B%5Cleft%28%5Cfrac%7B%5Csin%20%5Ctheta%7D%7B%5Ccos%20%5Ctheta%7D%5Cright%29%7D%3D%5Cfrac%7B%5Ccos%20%5Ctheta%7D%7B%5Csin%20%5Ctheta%7D)
Cos theta denoted as the ratio of adjacent to the hypotenuse.
![\cos \theta=\frac{\sqrt{15}(\text {Adjacent})}{8(\text {Hypotenuse})}](https://tex.z-dn.net/?f=%5Ccos%20%5Ctheta%3D%5Cfrac%7B%5Csqrt%7B15%7D%28%5Ctext%20%7BAdjacent%7D%29%7D%7B8%28%5Ctext%20%7BHypotenuse%7D%29%7D)
Therefore, find now as below,
![\cot \theta=\frac{\left(\frac{\sqrt{15}}{8}\right)}{\left(\frac{7}{8}\right)}=\frac{\sqrt{15}}{8} \times \frac{8}{7}=\frac{\sqrt{15}}{7}](https://tex.z-dn.net/?f=%5Ccot%20%5Ctheta%3D%5Cfrac%7B%5Cleft%28%5Cfrac%7B%5Csqrt%7B15%7D%7D%7B8%7D%5Cright%29%7D%7B%5Cleft%28%5Cfrac%7B7%7D%7B8%7D%5Cright%29%7D%3D%5Cfrac%7B%5Csqrt%7B15%7D%7D%7B8%7D%20%5Ctimes%20%5Cfrac%7B8%7D%7B7%7D%3D%5Cfrac%7B%5Csqrt%7B15%7D%7D%7B7%7D)